2012
DOI: 10.7498/aps.61.230504
|View full text |Cite
|
Sign up to set email alerts
|

Experimental confirmation on period-doubling bifurcation and chaos in dielectric barrier discharge in helium at atmospheric pressure

Abstract: A series of dielectric barrier discharge (DBD) experiments in helium at atmospheric pressure is carried out under a parallel electrode configuration. The discharge waveforms are observed in time-domain and analyzed in frequency-domain. Results show that under a certain condition the discharge can experience period-one, period-two and period-four discharges and finally enters into chaotic discharge as the amplitude of the driving voltage is increased. Our work verifies that the period-doubling route into chaos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The intrinsic feature of multipleperiod discharge has been confirmed experimentally in a helium discharge. [28] When the frequency is high enough, a stable symmetric discharge with similar characteristics to the radiofrequency discharge takes place, as shown in Fig. 7(c).…”
Section: Resultsmentioning
confidence: 84%
“…The intrinsic feature of multipleperiod discharge has been confirmed experimentally in a helium discharge. [28] When the frequency is high enough, a stable symmetric discharge with similar characteristics to the radiofrequency discharge takes place, as shown in Fig. 7(c).…”
Section: Resultsmentioning
confidence: 84%
“…In our previous work on a DBD in helium at atmospheric pressure [19], period-one, period-two, period-four and chaos can be successively observed after the gas breaks down by continuously increasing the amplitude of the applied voltage and remaining the other parameters unchanged.…”
mentioning
confidence: 89%
“…In the previous work, it has been numerically shown that the discharge can undergo a transition from a normal period-one operation to chaos via period-doubling bifurcation as the frequency [7][8][9][10][11] or the amplitude [12,13] of the applied voltage is increased, or via a route of a quasiperiodic torus by increasing the driving frequency [14]. Moreover, experimental observations (a) E-mail: ddai@scut.edu.cn on period-doubling bifurcation and chaos in atmospheric plasma jets [15][16][17][18] and in DBDs at atmospheric pressure under a parallel electrode configuration [19] are reported which confirm the existence of such nonlinear phenomena in a real experimental implementation.…”
mentioning
confidence: 99%
“…Recently, these nonlinear behaviors have been widely observed by numerical simulation and experiment. [7][8][9][10][11] Significant advances have been made both in their fundamental mechanism and in their dependence on the discharge parameters. But most of these papers focused on the parallel plate structure and needle-plate structure.…”
Section: Introductionmentioning
confidence: 99%